2017
DOI: 10.3390/rs9121210
|View full text |Cite
|
Sign up to set email alerts
|

New Scheme for Validating Remote-Sensing Land Surface Temperature Products with Station Observations

Abstract: Continuous land-surface temperature (LST) observations from ground-based stations are an important reference dataset for validating remote-sensing LST products. However, a lack of evaluations of the representativeness of station observations limits the reliability of validation results. In this study, a new practical validation scheme is presented for validating remote-sensing LST products that includes a key step: assessing the spatial representativeness of ground-based LST measurements. Three indicators, nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Nevertheless, because of the strong heterogeneity of land surface pattern, the accuracy of LST must be retrieved at 1K or better [7]. Thus, a large number of studies have focused on retrieval algorithms [7,12,13] and new validation schemes of LST [14][15][16]. Some studies indicated that location, land cover, vegetation fraction, and elevation had important influences on LST [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because of the strong heterogeneity of land surface pattern, the accuracy of LST must be retrieved at 1K or better [7]. Thus, a large number of studies have focused on retrieval algorithms [7,12,13] and new validation schemes of LST [14][15][16]. Some studies indicated that location, land cover, vegetation fraction, and elevation had important influences on LST [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…LST products were validated with field campaigns and radiance-based validation studies and errors are within ± 0.6°C in most cases in the global (Wan 2014). Besides, the mean bias of the MODIS LST product was less than 1°C in Northwest China (Li et al 2014;Yu et al 2017;Duan et al 2018). The MODIS LST product has applicability in comparison of LST over different LCTs in our study area.…”
Section: Data Collection and Methodologymentioning
confidence: 69%
“…The study area covers 3285 km 2 and ranges in elevation from 2538 to 4615 m. As a climatic and geographical transition zone, the study area provides an ideal testing ground with complex land surface characteristics for verifying the rationality of the proposed LST fusion framework. Many scholars have verified the applicability of satellite-derived LSTs in this region, and the results showed that root mean square error (RMSE) was generally within 5K [ 42 , 58 , 59 , 60 ]. Besides, a large number of aeronautical experiments have been carried out in the HRB [ 61 ], and some ground observations can be provided to validate the fusion result and analyze the uncertainty.…”
Section: Methodsmentioning
confidence: 99%